Thermal field study and analysis in hybrid solar flue gas chimney power plant - Aja, Aja; Alkayiem, H.; Karim, Z. (2011)
The concept of using flue gas waste heat as a backup in a solar chimney power plant is driven by the objective of solar chimney plant performance enhancement. This paper presents experimental results of thermal field of hybrid solar-flue-gas chimney power plant at different mode (solar mode, hybrid mode and flue gas mode). The experimental test rig consisted of two inclined absorber plate and diffuser surface with total area of 3.15 m 2 , flue gas channel (1m 3m 0.05m), greenhouse (air flow channel of 1m 3m 0.16m at inlet and 1m 3m 0.075m at exit), chimney of diameter 0.15m and height of 4m, flue gas inlet diffuser (1m 0.3m 0.05m) and flue-gas source (biomass burner coupled with centrifugal blower powered using a variable speed motor). The temperature distribution in the hybrid solar-flue gas chimney power plant test-rig was measured. Temperature difference between the chimney base (absorber plate exit air) and the ambient were studied which is the driving force in solar chimney power plant. On solar mode, the driving force (temperature difference between the absorber plate exit air and the ambient air) gave a maximum dT of 27.6 °C at irradiance of 797 W/m 2 . With flue gas as thermal backup during the day, maximum dT reached 38.1°C for inlet flue-gas temperature of 101.6 °C and irradiance of 672 W/m 2 , with flue gas as the only source of thermal energy (night mode), the temperature difference, dT, got up to 25.9 °C at a flue-gas inlet temperature of 107.6 °C. The solar mode experiment carried out after night mode experiment shows that the dT of the system the next day was enhanced as the temperature difference increased from sunrise contrary to the low temperature raise experienced on normal solar day.